2013
DOI: 10.1371/journal.pone.0079234
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkylated Aminoacyl sulfamoyladenosines as Potential Inhibitors of Aminoacylation Reactions and Microcin C Analogues Containing D-Amino Acids

Abstract: Microcin C analogues were recently envisaged as important compounds for the development of novel antibiotics. Two issues that may pose problems to these potential antibiotics are possible acquisition of resistance through acetylation and in vivo instability of the peptide chain. N-methylated aminoacyl sulfamoyladenosines were synthesized to investigate their potential as aminoacyl tRNA synthetase inhibitors and to establish whether these N-alkylated analogues would escape the natural inactivation mechanism via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These results also show that our approach of substituting the N 6 -position was the correct one, as only a limited reduction of the enzyme inhibitory activity was observed. This is in stark contrast to our previous efforts of methylating the alpha-amine, which was accompanied with a dramatic loss in inhibitory activity [37]. The adenine moiety seems not to be essential to generate high affinity molecules against class I aaRS, as it can be readily substituted with other nucleobases or even tetrazole moieties while still showing good inhibitory activity [11,38].…”
Section: Discussionmentioning
confidence: 57%
“…These results also show that our approach of substituting the N 6 -position was the correct one, as only a limited reduction of the enzyme inhibitory activity was observed. This is in stark contrast to our previous efforts of methylating the alpha-amine, which was accompanied with a dramatic loss in inhibitory activity [37]. The adenine moiety seems not to be essential to generate high affinity molecules against class I aaRS, as it can be readily substituted with other nucleobases or even tetrazole moieties while still showing good inhibitory activity [11,38].…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that E. coli MccE and RimL, two acetyl-CoA-dependent acetyltransferases, are able to detoxify several nonhydrolyzable aminoacyl adenylates including both natural McC, albomycin, and synthetic non-hydrolyzable aminoacyl adenylates (for instance, aspartyl-sulfamoyl adenosine) in a mechanism to protect bacteria from various toxic aminoacyl nucleotides [ 155 , 157 , 158 ]. To prevent this resistance mechanism, Vondenhoff et al synthesized N-methylated congeners for LSA and GSA (glycyl-sulfamoyl adenosine) but observed a significant reduction in inhibitory activity, showing that even a small modification of this amine is detrimental to binding [ 159 ]. However, the aforementioned carboxymethyl cytidine-containing McC analog ( Figure 9 a) has been shown to be resistant to MccE catalyzed N-acetylation [ 134 ].…”
Section: Natural and Synthetic Aarss Inhibitors And Their Inhibitomentioning
confidence: 99%
“…(Figure 55). 240 The authors believed that these modifications would potentially help to escape the natural inactivation mechanism of acetylation of the amino group and/or prevent the in vivo ( Figure 56). 241 The rationale was that the lack of the oxygen would improve the stability of the resulting aminoacyl sulfamate analogues while making the C-5' less electrophilic and prone attackby N 3 adenine, thus avoiding the formation of a cyclic degradation product.…”
Section: Ribosomal Peptidyl Center Inhibitorsmentioning
confidence: 99%
“…turned their attention to another class of microcin C analogues with a preserved nucleoside core but with the siderophore portion modified with N -methyl or d -amino acids (Figure ). The authors believed that these modifications would potentially help to escape the natural inactivation mechanism of acetylation of the amino group and/or prevent the in vivo instability of the peptide chain. A series of N -methyl and d -aminoacyl, sulfamoyl adenosine analogues 112a – d , 113a – e were prepared and investigated as potential aaRSs inhibitors.…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%